Development of N-doped bamboo-shaped carbon nanotube/magnesium oxide nanocomposites. (March 2020) - Vanyorek, László; Prekob, Ádám; Sikora, Emőke; Muránszky, Gábor; El Mrabate, Bilal; Udayakumar, Mahitha; Pekker, Péter; Viskolcz, Béla; Németh, Zoltán
Nitrogen-doped bamboo-shaped carbon nanotubes/magnesium oxide composites were prepared using a simple impregnation method. Magnesium oxide nanoparticles with different crystal morphologies were obtained using magnesium oxide powder and stearic acid precursors. The calcination of bamboo-shaped carbon nanotubes/magnesium stearate mixture in a 1:1 ratio with different temperatures (300 and 400℃) in an inert atmosphere was carried out. The prepared composites were further analyzed by X-ray powder diffraction, energy dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, specific surface area measurement, Fourier transform infrared spectroscopy, transmission and scanning electron microscopy and thermogravimetric analysis techniques. Results revealed that the characteristic morphology and the crystal structure of the composites rely primarily on the heat treatment temperature chosen. To obtain a proper crystalline magnesium oxide, at least 400℃ is required. As-prepared bamboo-shaped carbon nanotube-based composites would be an ideal candidate as a catalyst or a membrane additive material for water purification technology.